How does the ergogenic benefits, consumption, and overall perspective of caffeine differ between athletes in different perspective of caffeine differ between athletes in different sports? - Laflamme, S. (Gardner-Webb University, 2023)
Caffeine has been a very popular ergogenic aid that has been widely used by athletes at all levels of sports performance (Pickering & Grgic, 2019). The effects of caffeine have shown performance-enhancing symptoms among athletes along with multiple cognitive benefits such as reaction time and overall mood during exercise. According to McArdle, Katch, and Katch (2015), caffeine acts as a stimulant for the central nervous system. It acts as a blocker for adenosine receptors and allows for more neuron firing in the brain as well as increased blood flow from the heart to other body systems. In interest of caffeine`s ergogenic effect and overall improvement of performance, there has been several research studies that aim to prove whether caffeine makes a significant difference in quality of athletic performance. Further research is needed to conclude whether these factors affect the benefit of caffeine in everyday athletic performance as well as caffeine use in a competitive field. Therefore, the aim of this study was to determine the ergogenic effects of caffeine among male and female collegiate athletes and how these effects can be correlated to school schedule, hours of practice, competition usage, as well as side effects. It was hypothesized that caffeine will be a very common agent in the benefit of student athletes across a variety of sports with different intended purposes.